Phytochemical study and biological activities of garcinia nervosa (clusiaceae) / Nurr Maria Ulfa Seruji - Seruji, Nurr Maria Ulfa (2017)
Although there were many studies conducted on the Garcinia species, but there are very few studies reported on Garcinia nervos, especially Garcinia nervosa from Sarawak since it has not been explored yet. Garcinia nervosa (Clusiaceae) was investigated for its chemical constituents and biological activities. Seven chemical constituents were successfully isolated and identified for the first time from Garcinia nervosa where six are well known compounds, including ferulic acid (154), 3, 4-dimethoxycinnamic acid (155), 3-O-acetyloleanolic acid (156), scopoletin (157), stigmasterol (128) and friedelin (127). However, 3, 4-dimethoxycinnamic acid, 3-O-acetyloleanolic acid and scopoletin were isolated from Garcinia genus for the first time together with the unknown compound (E)-2-methyl-6-(1,6,6,12a-tetramethyl-7-o -xo-1,2,3,3a,5,5a,6,7,8,9,10,11,12,12a-tetrahydrocyclopenta []-cyclopropa[]phenanthren- 1yl)hept-2-enoic acid (158). The structural elucidation was obtained from the spectroscopic data of 1D and 2D nuclear magnetic resonance (1H NMR, 13C NMR, HMBC, and HMQC), ultra-violet (UV), Infra-red (IR), mass spectroscopy (MS) and comparison with literature data. The methanolic extracts and the major compounds of Garcinia nervosa was evaluated for total phenolic content, free radical scavenging activity, anti-inflammatory, cytotoxicity and antibacterial activities. The bark extracts exhibited higher total phenolic contents than the leaves extracts. Both of the extracts showed very strong antioxidant activity and anti-inflammatory activity. Moreover, in the cytotoxicity assay, the barks extract gave weak inhibition against the three cell lines while twigs showed weak inhibition to MCF-7 (human breast cancer cell lines) and HT-29 (human promyelocytic leukemia) but not active for HeLa (cervical cancer cell lines) and leaves extracts showed inactive cytotoxic activity against all the tested cancer cell lines. The antimicrobial activity which was measured by minimum inhibitory concentration (MIC) and minimum bacterial concentration (MBC) for the extracts and the major pure compounds exhibited the activity with the minimum concentration ranging from 450 to 112.5 (g/ mL). This study finding provide useful information to the chemotaxonomy of Garcinia for further biotechnology research and development which in line with National Biotechnology Policy.